Dekonstruksi Homo Ekonomicus menuju Homo Spiritus Akuntan Publik yang Beretika - Nursanty, Ida Ayu; Prathama, Baiq Destania; Kartini, Endang; Mutia, Galuh Ratna (Valid: Jurnal Ilmiah, 2024)
This research examines the deconstruction of homo economics towards the concept of homo spiritus as an ethical accountant. The concept of Homo Spiritus in this study refers to an individual with holistic consciousness who completely obeys God's will based on conscience, or is often referred to as the God Spot. The research method used in this study is Rationalist Spiritualist, namely the idea that finding true truth can only be achieved through mind control. Spiritualist thoughts are thoughts that are controlled and born from a heart that has been purified and intact, which will ultimately be reflected in work and provide benefits to other people. Research related to the spiritualist paradigm has not been widely carried out, so researchers are trying to enrich this understanding and contribute a spiritualist perspective within the scope of qualitative research. This study finds that the concept of Homo Economicus, which focuses on rationality and self-interest, is often criticized for being limited to the goal of personal prosperity. Therefore, a new concept is needed to direct accountants to ideal qualities, namely by making Homo Economicus the initial stage towards Homo Spiritus, a more basic concept for achieving a more just and prosperous life